Segregation of the Qb‐SNAREs GS27 and GS28 into Golgi Vesicles Regulates Intra‐Golgi Transport. (1st March 2013) - Fusella, Aurora; Micaroni, Massimo; Di Giandomenico, Daniele; Mironov, Alexandre A.; Beznoussenko, Galina V.
<x xml:space="preserve">Abstract</x> The Golgi apparatus is the main glycosylation and sorting station along the secretory pathway. Its structure includes the Golgi vesicles, which are depleted of anterograde cargo, and also of at least some Golgi‐resident proteins. The role of Golgi vesicles remains unclear. Here, we show that Golgi vesicles are enriched in the Qb‐SNAREs GS27 (membrin) and GS28 (GOS‐28), and depleted of nucleotide sugar transporters. A block of intra‐Golgi transport leads to accumulation of Golgi vesicles and partitioning of GS27 and GS28 into these vesicles. Conversely, active intra‐Golgi transport induces fusion of these vesicles with the Golgi cisternae, delivering GS27 and GS28 to these cisternae. In an in vitro assay based on a donor compartment that lacks UDP‐galactose translocase (a sugar transporter), the segregation of Golgi vesicles from isolated Golgi membranes inhibits intra‐Golgi transport; re‐addition of isolated Golgi vesicles devoid of UDP‐galactose translocase obtained from normal cells restores intra‐Golgi transport. We conclude that this activity is due to the presence of GS27 and GS28 in the Golgi vesicles, rather than the sugar transporter. Furthermore, there is an inverse correlation between the number of Golgi vesicles and the number of inter‐cisternal connections under different experimental conditions. Finally, a rapid block of the formation of vesicles via COPI through degradation of ϵCOP accelerates the cis‐to‐trans delivery of VSVG. These data suggest that Golgi vesicles, presumably with COPI, serve to inhibit intra‐Golgi transport by the extraction of GS27 and GS28 from the Golgi cisternae, which blocks the formation of inter‐cisternal connections.